2017
DOI: 10.7150/thno.18752
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Natural Killer Cells Exert Therapeutic Effect in Melanoma

Abstract: Objective: Exosomes are nanovesicles that are released from normal and tumor cells and are detectable in cell culture supernatant and human biological fluids. Although previous studies have explored exosomes released from cancer cells, little is understood regarding the functions of exosomes released by normal cells. Natural killer (NK) cells display rapid immunity to metastatic or hematological malignancies, and efforts have been undertaken to clinically exploit the antitumor properties of NK cells. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
327
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(365 citation statements)
references
References 50 publications
12
327
0
2
Order By: Relevance
“…Their therapeutic effect was also studied using NK cell lines as exosome producers to facilitate cell expansion for vesicle retrieval. Exosomes from the NK-92MI cell line showed remarkable cytolytic activity against melanoma (23) and glioblastoma (24), while EVs from in vitro expanded NK cells cocultured with K562.mbIL21 cells displayed antitumor activities against acute lymphoblastic leukemia and breast carcinoma (25). Apart from a consistent equipment of molecules aimed at target killing, NKEVs were also found to contain miR-186, a tumor suppressor micro-RNA that contributes to their cytostatic effects in neuroblastoma and prevents the inhibitory effects on NK cells of transforming growth factor beta (TGFβ) (26).…”
Section: Introductionmentioning
confidence: 99%
“…Their therapeutic effect was also studied using NK cell lines as exosome producers to facilitate cell expansion for vesicle retrieval. Exosomes from the NK-92MI cell line showed remarkable cytolytic activity against melanoma (23) and glioblastoma (24), while EVs from in vitro expanded NK cells cocultured with K562.mbIL21 cells displayed antitumor activities against acute lymphoblastic leukemia and breast carcinoma (25). Apart from a consistent equipment of molecules aimed at target killing, NKEVs were also found to contain miR-186, a tumor suppressor micro-RNA that contributes to their cytostatic effects in neuroblastoma and prevents the inhibitory effects on NK cells of transforming growth factor beta (TGFβ) (26).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have discovered that natural killer (NK) cells may be associated with the immune response against tumors . NK‐92 cell line‐derived exosomes exert cytotoxic effects against melanoma, which are partly associated with the functional protein, FasL . These findings suggest that interaction between melanoma and other immune cells can also influence the pathogenesis of melanoma, both beneficially and pathologically.…”
Section: Importance Of Exosomes In Skin Tumorsmentioning
confidence: 98%
“…NK cells exert rapid immune effect to metastatic or hematological malignancies, which have been confirmed and clinically exploited the antitumor characteristics. Zhu et al . explored that NK‐92MI cells produce exosomes with two functional NK proteins, perforin, FasL and secreted tumor necrosis factor (TNF)‐alpha, which affected the cell proliferation, to exert cytotoxic effects on melanoma cells without side effects.…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…NK cells exert rapid immune effect to metastatic or hematological malignancies, which have been confirmed and clinically exploited the antitumor characteristics. Zhu et al 77 explored that NK-92MI cells produce exosomes with two functional NK proteins, perforin, FasL and secreted tumor necrosis factor (TNF)-alpha, which affected the cell proliferation, to exert cytotoxic effects on melanoma cells without side effects. Furthermore, Wu et al 78 studied NK cell-derived exosomes and their result revealed that at NK-derived exosome presented perforin, granzyme A, granzyme B, granulysin and FasL could mediate cytotoxicity against cancer cells via caspase-independent and caspase-dependent cell death signaling pathways.…”
Section: Exosomes and Antitumor Immune Responsementioning
confidence: 99%